PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASIONAL, DAN JOB INSECURITY TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Pradnyawati, Ni Made Saras; Dewi Adnyani, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023, 2023)
The aim of this study was to analyze the effect of job satisfaction, organizational commitment, and job insecurity on organizational citizenship behavior (OCB) conducted at the Office of Public Works and Spatial Planning, Jembrana Regency. This study was conducted using a saturated sampling technique of 45 people with the contract employee status. Data eliciting was done by interview method and distributing questionnaires. The data analysis technique that used in this study is multiple linear regression analysis. The results of this study indicated that job satisfaction has a significant positive effect on OCB, organizational commitment has a significant positive effect on OCB, while job insecurity has a significant negative effect on OCB. The results of this study provide evidence on the development of human resource management science and organizational behavior science, especially regarding OCB, job satisfaction, organizational commitment, and job insecurity which are able to prove empirically the theory used in this study refers to the social exchange theory is a theory that assumes that the relationship between agencies and employees is a form of social exchange. This research can be used as a reference for all parties, both for students or universities in conducting research with similar variables and for agencies in improving OCB behavior.